2020
DOI: 10.1002/lno.11642
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom species loss in phytoplankton communities and its effect on ecosystem functioning

Abstract: The effects of species diversity on ecosystem functioning have been broadly studied, mostly considering random artificial assemblages. However, natural communities are shaped by ecological interactions and environmental conditions often leading to nonrandom species extinctions. Here, we manipulated a natural phytoplankton community by generating a taxonomic diversity gradient based on rare species exclusions and conducted a mesocosm experiment to investigate the diversity effects on ecosystem functioning (reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…By revealing that predators can mitigate the destabilizing effects of heatwaves on multitrophic stream communities, our study adds to a growing body of literature exploring the contribution of individual species to the stability of communities, ecosystem functioning and service supply (Gerhard et al, 2020;Kordas et al, 2017;Oliver et al, 2015;Post & Pedersen, 2008;Ross, Arnoldi, et al, 2021;Smale et al, 2019;White et al, 2018White et al, , 2020Worm et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…By revealing that predators can mitigate the destabilizing effects of heatwaves on multitrophic stream communities, our study adds to a growing body of literature exploring the contribution of individual species to the stability of communities, ecosystem functioning and service supply (Gerhard et al, 2020;Kordas et al, 2017;Oliver et al, 2015;Post & Pedersen, 2008;Ross, Arnoldi, et al, 2021;Smale et al, 2019;White et al, 2018White et al, , 2020Worm et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…Biodiversity change across the globe is a non-random process (Chen et al, 2020;Estes et al, 2011;Gerhard et al, 2020;Gross & Cardinale, 2005;Purvis et al, 2000). Of particular concern is trophic downgrading, whereby species extinctions follow a pattern of systematic community disassembly starting from the highest trophic levels, as a result of the larger body sizes, metabolic demands and resource requirements of apex predators (Estes et al, 2011;Tanentzap et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Coadaptation might thus facilitate coexistence but weaken diversity effects, explaining some variation in the strength and direction of BEF relationships among studies (Aubree et al., 2020; Chen et al., 2019). For instance, artificially assembled communities might contain species with greater trait diversity than natural communities that have been exposed to longer environmental filtering (Gerhard et al., 2021). Since our experiment only covered ~10 generations, evolutionary changes probably played a minor role.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity gradient (six levels, increasing in diversity from the lowest diversity at D1 to the highest at D6) was generated by dilution of the natural community (dilution factors ranged from 1:1 × 10 5 to 1:1) and thus removal of rare species (Engel et al, 2017;Hammerstein et al, 2017). Each diversity level was incubated in flasks for 26 days to increase biomass prior to the start of the experiments (for methodological details, see Gerhard et al, 2020). The dilution created a diversity gradient that was maintained during the incubation until the inoculation in the mesocosm and the microcosm experiment, and therefore the diversity manipulation was based on the initial pool of species (Figure 2).…”
Section: General Experimental Set-upmentioning
confidence: 99%
“…In a previous mesocosm study, we showed that the loss of rare species does not result in a significant decay in RUE and standing biomass as long as the common or abundant species are maintained, considering two nutrient levels (Gerhard et al, 2020). Here, we investigated the effect of the rare species loss combined with a wide N:P supply ratios) and the diversity of (natural) communities experimentally, which is conceptually understood but poorly tested for phytoplankton.…”
Section: Introductionmentioning
confidence: 97%